Comparison of the influence of heat-treatment and cold-treatment treatments associated with kinesitherapy on the functioning of patients with gonarthrosis - Kałużna, Anna; Kola, Katarzyna; Kitschke, Ewa; Kałużny, Krystian; Żukow, Walery (Journal of Education, Health and Sport, 2018)
The aim of this study was to compare the effects of rehabilitation in people burdened with osteoarthritis of the knee after using active exercises in the relief associated with the physiotherapy - mud containing minerals (fango) or local cryotherapy.Studies were conducted in two groups before and after a ten-day improvement period. The assessment was based on the subjective perceptions of the VAS participants as well as completed questionnaires. In the assessment of the objective range of mobility of knee joints, angular measurements of flexion and straightening of the joint, as well as the "Get up" test were performer to check the overall motor efficiency of the patients. The results of the study have shown that the use of appropriately selected physiotherapy in knee osteoarthritis significantly alleviates pain and improves the overall condition of patients suffe ring from this condition.